Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

If f(x) = 11 - 6(x - 8), what is f(-3)?


Sagot :

Answer:

We conclude that:

  • [tex]f\left(-3\right)=77[/tex]

Step-by-step explanation:

Given the function

[tex]f(x) = 11 - 6(x - 8)[/tex]

Important Tip:

  • In order to determine f(-3), all we need is to substitute x = -3 in the function equation

substitute x = -3 in the equation

[tex]f(x) = 11 - 6(x - 8)[/tex]

[tex]f(-3) = 11 - 6(-3 - 8)[/tex]

[tex]f\left(-3\right)\:=\:11-\left(-66\right)[/tex]

[tex]f\left(-3\right)\:=\:11+66[/tex]               ∵ Apply rule  -(-a) = a

[tex]f\left(-3\right)=77[/tex]

Therefore, we conclude that:

  • [tex]f\left(-3\right)=77[/tex]